Dynamic hardness of cemented tungsten carbides. (September 2018) - Hanner, Luke A.; Pittari, John J.; Swab, Jeffrey J.
Abstract: Cemented tungsten carbides are composed of a hard tungsten carbide (WC) phase held together by a soft, ductile binder phase, typically cobalt (Co). This study examines the role of the binder composition and content on the Knoop hardness at quasi-static and dynamic strain rates. Seven different tungsten carbide materials were tested: four WC-Co systems containing 10%, 15%, 20% and 25% cobalt, two with a chromium‑nickel alloy binder phase, and one "binderless" tungsten carbide. Quasi-static Knoop hardness testing was performed at strain rates of 10 −3  s −1 and at indentation loads between 300 and 30, 000 g using a Wilson Tukon 2100 unit. Dynamic Knoop hardness testing was conducted at strain rates of 10 3  s −1 using a Dynamic Indentation Hardness Tester over a range of indentation loads. All of the materials exhibited a rate-dependent Knoop hardness, with the hardness increasing by up to 60% with increasing strain rate. Highlights: Seven cemented carbide materials were evaluated for indentation hardness under quasi-static and dynamic testing conditions. Dynamic hardness was measured at strain rates of ~ 10 3  s −1 with an apparatus based on Kolsky pressure bar principles. All of the tungsten carbide materials exhibited a rate-dependent Knoop hardness value. The change in Knoop hardness from quasi-static to dynamic was observed to grow with an increasing amount of binder phase.